Issues & Observations the More Things Change ... - Campbell, David (Center for Creative Leadership, 2008)
The piece contains a series of observations on leadership, all of which I find today are still relevant. Consequently, it seems worth reviving even though it was written fourteen years ago. There is no doubt that much about leadership has changed and continues to change; at the same time there is also much that is perpetual.
Online resource; Title from title page (viewed January 1, 2008)